Scarcity and World Oil Prices - Adelman, M. A. (The Review of Economics and Statistics, 1986)
The current (Summer 1985) world oil price, and changes since 1973, cannot possibly be explained by scarcity, or by changes in scarcity. The level and dispersion of marginal costs, and the pattern of investment behavior since 1973, prove that supply is being restricted to maintain the price, which can be maintained so long as the low-cost oil is dammed up. If the dam breaks, so will the Statement of the Problem M X ANY public and private investment decisions, affecting a significant fraction of world income, depend on the expected price of crude oil. Since the price explosion of 1973, and especially since the second explosion of 1979, there has been a wide consensus: Oil has become, and will continue to be, in increasingly short supply for the rest of the century. Further price increases are necessary and inevitable. We need cite only a fraction of even the post1978 predictions of rising oil prices, which were and are used as a basis for private and public investment, and taxation. (U.S. CIA, 1979, p. iii; Fesharaki, 1980; U.S. Senate, 1982; OGJ, 1982, pp. 118, 210; OGJ, 1984a, p. 32; Canada, 1980, 1981a, 1981b.) The price decline since 1980-81 has not weakened the consensus, but has lowered the rate of expected increase. Prices are expected to be weak or stable for a few years, then begin the inexorable increase. (EMF 6, 1982; US. GAO, 1983; World Bank, 1983, p. 28; and 1985, pp. 37-38; New York Times, 1984; DOE, 1985; Erickson, 1985; Saunders, 1984.) The oil-company acquisitions of 1983-84 were obviously based on the consensus view. An expert panel convened by the CIA in April 1985, like one convened by the California Energy Commission, expected that prices would rise, at an increasing rate, starting around 1990. (Wall Street Journal, 1985; California, 1985.) The International Energy Workshop of the International Institute of Applied Systems Analysts compiled a consensus forecast in December 1981, July 1983, and July 1985. The first consensus was that the price would nearly equal $60 in 1990; the most recent has it approaching that number only by 2010. A twenty-year postponement is no small change, of course. But in each case, the consensus was that the current price of oil was approximately equal to, or mildly above, the scarcitydetermined price. In the long run, it would have to rise above the current level. (Manne and Nordhaus, 1985; it should not be assumed that they themselves share the consensus, or that they do not.) The Economic Theory of the Consensus In general, absent monopoly restriction of output, a rising price registers increasing scarcity as consumption puts increasing strain upon productive resources. Some formal oil price models are explicitly competitive. (Mead, 1979, 1985; Cremer and Salehi-Isfahani, 1980; MacAvoy, 1982; Roumasset et al., 1983). More often, competition is an implicit major premise. Prices are said to reflect not monopoly but forces or deeper forces. Or it is said that if the cartel of producing nations (not the unimportant organization OPEC) disappeared, oil prices would not be strikingly different from what they are. Or that discoveries had been shrinking, and demand increasing up to 1973, hence prices had to rise, so at most the cartel pushed them up a bit faster. Other models are non-committal, but implicitly competitive, in that they have price driven by total consumption pressing against reserves. Figure 2 does not, of course, disprove this proposition but it does suggest that if scarcity pushed up prices, scarcity must have been very sudden and strong. There have also been attempts to model the oil market as a monopoly, in the generic sense: a few Received for publication June 24, 1985. Revision accepted for publication November 19, 1985. * Massachusetts Institute of Technology. The research for this paper has been supported by the National Science Foundation, grant SES-8412971, and by the Center for Energy Policy Research of the M.I.T. Energy Laboratory. I am obliged to Michael C. Lynch for valuable assistance. For many helpful comments and criticisms, I am indebted to Paul G. Bradley, Harry G. Broadman, Richard L. Gordon, William W. Hogan, Gordon M. Kaufman, Stephen Martin, James W. McKie, Joe Roeber, James L. Smith, G. Campbell Watkins, and to two anonymous referees. But any opinions, findings, conclusions or recommendations expressed herein are those of the author, and do not necessarily reflect the views of the NSF or any other person or group. Copyright ? 1986 [ 387 ] This content downloaded from 157.55.39.17 on Wed, 31 Aug 2016 04:37:42 UTC All use subject to http://about.jstor.org/terms 388 THE REVIEW OF ECONOMICS AND STATISTICS sellers restraining output and raising prices. (For an excellent survey, see Gately (1984).) But these models are also based on rising scarcity. They aim to show the difference between the competitive response and the monopoly response. Perhaps, given the increasing scarcity inherent in an exhaustible natural resource... there is a very limited scope for the monopolist ... indeed, under the natural 'first approximation' of constant elasticity demand schedules, with zero extraction costs, monopoly prices and competitive equilibrium prices will in fact be identical (Stiglitz,